Evaluation of the Activity of Some Plants Extracts on Thyroid Gland Regulation in Female Albino Rats - Hameed, Shahad Imad; Al-Shahwany, Ayyad W.; Salih, Sabah Jawad (Iraqi Journal of Science, 2020)
This study sheds light on various drugs of plant origin which have shown action on thyroid and its functioning as well as on the various factors associated with thyroid dysfunction. Therefore, the aim of this study is to determine the activity of the aqueous extracts of Fucus vesiculosus, Coleus forskohlii, Curcuma longa L., Rosmarinus officinalis L., Camellia sinensis L. and Melissa officinalis L. in regulation of thyroid hormones in serum taken from rats. Fifty-seven female albino rats were divided into 19 groups, each group with 3 rats, and treated orally with an aqueous plant extract in three different doses, except the control group which was treated with normal saline only. Also, a histological study was conducted on the thyroid gland after short-term treatment with different doses of these extracts. The results demonstrated that 5mg/kg of Curcuma longa was the most powerful extract which increased T3 level in a rats serum by 25% compared with the control treatment. Also, the most effective dose which increased T4 level was 1000mg/kg of Coleus forskohlii, which increased the hormone level by 7% compared with the control. Meanwhile, 1000mg/kg of Coleus forskohlii was the effective extract which reduced TSH level by 61% compared with the control. While, the extract of Rosmarinus officinalis 220mg/kg reduced T3 and T4 levels in the serum of rats by 56% and 17% respectively. However, oral administration with Camellia sinensis 1.25mg/kg increased TSH level by 10% compared with the control. The obtained data demonstrated that Curcuma longa and Coleus forskohlii, at low doses, can be very effective for completely treating hypothyroidism in rats.The findings of this study propose that the extracts may have the property to regulate thyroid levels in rats.